Assessment of control strategies for fault ride through of SCIG-based wind energy conversion systems. (1st January 2016) - Manaullah,; Sharma, Arvind Kumar
ABSTRACT: With increasing penetration of wind energy into the power grid, researchers have started focusing more on control and coordination of wind energy conversion systems (WECS) with the other components at system level, especially during fault. It is important to implement a suitable fault ride through control strategy to avoid tripping of the generators when the power system is subjected to voltage dips normally below 90% of nominal voltage. The dips below 90% may lead to a significant loss of generation and frequency collapse, followed by a blackout. This article implements and assesses the methodologies to deal with such situations for squirrel cage induction generator-based wind energy conversion systems employing fully rated power electronic converters. Three distinct control techniques—namely, balanced positive sequence control, positive negative sequence control, and dual current control—have been simulated and applied to grid side converter of SCIG-based WECS. The performance of all the three control strategies has been compared and presented in this work. During this study, the system is subjected to the most common unsymmetrical line to ground (LG) fault and most severe symmetrical LLL fault on grid for the purpose of anaysis.